Inflammatory Cytokines, Immune Cells, and Organ Interactions in Heart Failure - Li, Huihui; Chen, Chen; Wang, Dao Wen (Frontiers in Physiology, 2021)
In spite of mounting evidence demonstrating the significance of inflammation in the pathophysiological mechanisms of heart failure (HF), most large clinical trials that targeting the inflammatory responses in HF yielded neutral or even worsening outcomes. Further in depth understanding about the roles of inflammation in the pathogenesis of HF is eagerly needed. This review summarizes cytokines, cardiac infiltrating immune cells and extra-cardiac organs that orchestrating the complex inflammatory responses in HF and highlights emerging therapeutic targets.